Motivation and Plan to Quit Smoking in Health Students in Aceh: A Qualitative Study - Mardhiah, Ainal; Sufri, Sofyan; Sitio, Roma; Niswah, Niswah; Desiana, Desiana (Journal of Health, Medicine and Nursing, 2025)
Smoking is one of the preventable causes of death. Indonesia is a country with the highest percentage of smokers in the world, thus threatening the health, safety and economic welfare of the people. One of the most important efforts to prevent these effects is to stop smoking. Quitting smoking will benefit all ages, quitting earlier will have greater benefits. Research objective: To describe motivation and plans to stop smoking among young people in Aceh. Materials and Methods: This study was an exploratory qualitative study conducted on smoking college students (15-24 year old group) with a total of 35 participants. Research will be carried out in Aceh in 2022.Data collection was carried out by way of Focus Group Discussion (FGD) which was divided into 5 FGD groups. The results of the FGD were then transcribed, followed by coding and determining the theme. Results: The results of this study obtained 4 themes: motivation to stop smoking, barriers to quitting smoking, reasons for failing to quit smoking, and method to quit. Motivations to stop smoking include smoking is harmful, increasing spending, and health. Barriers to stopping smoking include smoking has become a habit and addiction. The reason for failure to quit was reported because of a friend who was a smoker. The method chosen to quit smoking spontaneously. Conclusion: To stop smoking must be based on self-desire then supported by other external factors.